Diagnostic Yield of Blood Cultures among Patients Admitted with Non-Focal Pyrexias - Aliena Badshah; Ahmed Naseer; Imran Ullah; Muhammad Ishaq (Gandhara University, 2023)
OBJECTIVES To establish the diagnostic yield of blood cultures among patients admitted with non-focal pyrexias. METHODOLOGY This descriptive cross-sectional study was conducted in the Department of Medicine, Khyber Teaching Hospital, Peshawar, from August 2020 to April 2021. One hundred ninety-seven patients with non-focal pyrexia were recruited. Data about age, gender, presence of other illnesses like diabetes and hypertension, history of smoking and duration of fever were noted. A thorough clinical evaluation was done. Under aseptic conditions, 2 blood culture sets were taken. The final blood culture report was collected after 5 days of incubation in culture media. The culture was labelled positive if any organism was isolated from the sample. All data was entered in specially designed proforma. Patients with positive blood cultures were managed as per hospital protocols. Confidentiality of data was ensured. RESULTS Our study shows that among 197 patients, 18(9%) had positive cultures, while 179(91%) did not yield any pathogen on blood culture. Escherichia coli was the most commonly grown organism among the positive blood cultures. CONCLUSION The yield of blood culture was 9% in febrile patients admitted to the medical ward of a tertiary care hospital.